Correlation of Processing, Inner Structure, and Part Properties of Injection Moulded Thin-Wall Parts on Example of Polyamide 66 - Dietmar Drummer; Steve Meister (International Journal of Polymer Science)
In micro- and thin-wall injection moulding the process conditions affect the developed internal structures and thus the resulting part properties. This paper investigates exemplarily on polyamide 66 the interactions of different cooling conditions on the morphological and crystalline structures. The investigations reveal that a slow cooling rate of the melt results in a homogeneous morphology and a higher degree of crystallinity and also a favoured crystalline structure. Consequently, the dielectric behaviour and light transmitting part properties are affected.